PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP EFEKTIVITAS PENJUALAN DENGAN PENGENDALIAN INTERN SEBAGAI VARIABEL INTERVENING (SURVEI PADA KERAJINAN BATIK DI KOTA JAMBI) - Herawaty, Netty; Sari, Rizki Yuli (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
The purpose of this research is to analyze the influence of Accounting InformationSystems on Sales Effectiveness with Internal Control as Intervening Variable. Theanalysis method of research comprises influence test using multiple regressionanalysis, t-test, F-test, coefficient of determination. The research data are obtainedby questioner directly to the respondents. There are 39 batik craftsmen in Jambi city.The result of this research indicate that Accounting Information System has asignificant positive on Internal Control. Internal Control does not have influencesignificantly toward on Sales Effectiveness. and Accounting Information systemhave a significant positive on Sales Effectiveness as intervening variable.meanwhile, on the simultaneity test, all independent variables have a positive effecton Sales Effectiveness. (Survey on Batik Craft in Jambi City).